Growth and Nutrient Uptake Characteristics of Heterosigma akashiwo (Raphidophyceae) under Nitrogen and Phosphorus Concentrations in the East China Sea - Anqiang Yang (MDPI AG, 2021)
Heterosigma akashiwo is classified as a harmful algal bloom (HAB) species that frequently occurs in eutrophic coastal waters and results in the contamination and mortality of fish and shellfish. The growth of H. akashiwo in four phosphate and nitrate concentration scenarios, representing the observed nutrient concentration ranges in the East China Sea (ECS), was evaluated to further understand the effect of nutrient concentrations on H. akashiwo blooms. The specific growth rate in the exponential growth phase (µ′) and the maximum cell density were lower (17–21% and 41%, respectively) under low phosphorus concentration scenarios, compared to the rates observed under high phosphorus concentration scenarios. The cellular nitrogen-to-phosphorus ratios of H. akashiwo were influenced by the initially supplied N:P ratio and the allocation strategy employed. Phosphorus concentration had a greater influence on the total growth of H. akashiwo than nitrate did, within the natural nutrient conditions of the ECS. These results could serve as a reference for coastal water management and marine ecological management and may be useful for further studies on the simulation and prediction of H. akashiwo blooms, particularly in the ECS.